Update on migraine management. Issue 5 (25th May 2022) - Larkin, Lisa
Abstract : Migraine is a highly prevalent disorder in women associated with significant disability. Yet it remains underdiagnosed and undertreated. Recent advances in our understanding of the pathophysiology of migraine, including the role of calcitonin gene-related peptide, has led to the development of new targeted migraine therapies. It is important for all healthcare professionals caring for women to be familiar with the diagnostic criteria for migraine and for them to follow a stepwise approach to management of acute and chronic migraine that comprises biobehavioral and pharmacologic management, particularly the more recently approved therapies.